2015
DOI: 10.12788/jcso.0156
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bladder volume on radiation dose to the rectum in the definitive treatment of prostate cancer

Abstract: A greater bladder volume resulted in a reduced mean dose to the rectum irrespective of planning method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Frizzell B et al made a de nitive treatment for prostate cancer, according to the in uence of BV on rectal radiotherapy dose. The lling of bladder was compared with emptied bladder, the average exposure dose of rectum decreased by 27.6 Gy, and there was signi cant difference (P=0.031) [30]. Buchali et al found that when the BV increased, the exposure dose decreased.…”
Section: The Consistency Of Bv During Radiotherapymentioning
confidence: 99%
“…Frizzell B et al made a de nitive treatment for prostate cancer, according to the in uence of BV on rectal radiotherapy dose. The lling of bladder was compared with emptied bladder, the average exposure dose of rectum decreased by 27.6 Gy, and there was signi cant difference (P=0.031) [30]. Buchali et al found that when the BV increased, the exposure dose decreased.…”
Section: The Consistency Of Bv During Radiotherapymentioning
confidence: 99%
“…Despite no agreement on the embryonic origin of DVF, three theories including tension induction, mesenchyme, and peritoneal fusion all support the concept of DVF as a separate structure that neither belongs to the fascia propria of the rectum nor to the urogenital system[ 8 - 11 ]. Frizzell et al [ 12 ] observed that DVF fused with the anterior mesorectal fascia in imaging such as magnetic resonance imaging and therefore was difficultly differentiated and that the above two types of fascia exhibited a low-signal shadow of a single-layer linear structure after being reflected between the anterior rectal wall of the rectum and vagina, the seminal vesicle and the prostate, and peritoneum (Figure 1B ). Another researcher discovered that intraoperative observations (endorectal ultrasound) were completely consistent with the anatomical course of DVF and that DVF divided the rectum and urogenital organs into posterior prostatic space and anterior rectal space, among which the latter existed objectively as the anatomical plane of separation plane during TME.…”
Section: The Origin Basis and Clinical Anatomy Of Dvfmentioning
confidence: 99%